2019
DOI: 10.1111/jvim.15641
|View full text |Cite
|
Sign up to set email alerts
|

Enteroinsular axis response to carbohydrates and fasting in healthy newborn foals

Abstract: BackgroundThe enteroinsular axis (EIA) comprises intestinal factors (incretins) that stimulate insulin release after PO ingestion of nutrients. Glucose‐dependent insulinotropic polypeptide (GIP) and glucagon‐like peptide‐1 (GLP‐1) are the main incretins. The EIA has not been investigated in healthy neonatal foals but should be important because energy demands are high in healthy foals and dysregulation is frequent in sick foals.Objectives and HypothesisTo evaluate the EIA response to carbohydrates or fasting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(44 citation statements)
references
References 39 publications
5
36
3
Order By: Relevance
“…Minor changes in theses hormones were observed with PO carbohydrate challenges, which were more evident in response to nursing. Our results and those of previous studies from our laboratory 14…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Minor changes in theses hormones were observed with PO carbohydrate challenges, which were more evident in response to nursing. Our results and those of previous studies from our laboratory 14…”
Section: Discussionsupporting
confidence: 91%
“…These findings were contrary to our hypothesis, in which an increase in plasma glucagon concentration was expected in response to fasting so as to maintain euglycemia by glycogenolysis and gluconeogenesis. However, based on previous data, 14 knowledge, not previously reported in foals or horses. This finding also is intriguing because it was recently shown that immediately after nursing, healthy foals exhibited hyperglycemia that was followed by hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A 50% dextrose solution (300 mg/ kg) (VetOne, MWI Animal Health, Boise, Idaho, USA) was administered IV (time 0). The dose of dextrose administered was based on previous data from our laboratory [25], as well as preliminary data showing that this dose of dextrose (300 mg/kg) resulted in a tolerable level of hypoglycemia (without clinical signs) in response to insulin (Unpublished data, LDH & HMK). Blood samples were collected at -60, 0, 2, 5, 7, 10, 15,19,22,25,30,35,40,50,60,75,90,120,150, and 180 minutes relative to administration of dextrose.…”
Section: Experimental Designmentioning
confidence: 99%